Avoiding surveillance biopsy: Use of a noninvasive biomarker assay in a real‐life scenario. Issue 1 (24th November 2020) - Ang, Audrey; Schieve, Courtney; Rose, Stanley; Kew, Clifton; First, M. Roy; Mannon, Roslyn B.
Abstract: Purpose: TruGraf™ blood test measures a specific gene expression signature in peripheral blood mononuclear cells for noninvasive assessment of kidney transplant recipients (KTRs) with stable renal function, excluding subclinical acute rejection (subAR) with high degree of confidence. Study objective was to correlate TruGraf™ test with 6‐month surveillance biopsy (SBx). Methods: Prospective, single‐center study of 116 consecutive KTRs with SBx performed at 6 months post‐transplant..TruGraf™ done at time of SBx; results compared with histology (Banff 2017) for concordance. Results: Of 116 enrollees, 26 excluded, absent biopsy ( n  = 17), test quality control issues ( n  = 9), leaving 90 KTRs—66% deceased donor kidneys, 58% African American, and 59% male. TruGraf™ result negative in 67 subjects; 54 had normal biopsy, indicating SBx could have been avoided. Eight subjects had true positive result where biopsy justified. Unnecessary biopsy would have been performed in 15 subjects with false‐positive TruGraf™, and subAR missed in 13 subjects with false‐negative test. In overall population of 90 patients, SBx would have been avoided in 54 (60%). Conclusions: Implementation of TruGraf™ testing in a "real‐world" cohort at the time of SBx identified a significant proportion of KTRs that could have avoided SBx.